2021
DOI: 10.47750/cibg.2021.27.02.199
|View full text |Cite
|
Sign up to set email alerts
|

Turnover Intention and Procrastination: Causal Contribution of Work-Life (Im)Balance

Abstract: In the changing world of work, including increasing working parents and work from home, work-life balance is receiving increased attention from HR executives looking to improve employee productivity. Talent retention and getting active and responsible contributions from existing employees are permanent concern for organizations because of their high costs and negative consequences. This research aims to investigate the relationship of work-life balance with turnover intention and procrastination. The present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Zeelenberg and colleagues (2006) explained 'action effect' as an action that leads to failure will cause more regret than inaction that leads to similar failure. In recent work, Sharma and Sharma (2021) found that the (in)action state and negative emotion can lead to procrastination, and an effortful selfregulated coping mechanism is needed to overcome the inner resistance.…”
Section: Emotional Reaction-handling Action Orientation and Wisdommentioning
confidence: 99%
“…Zeelenberg and colleagues (2006) explained 'action effect' as an action that leads to failure will cause more regret than inaction that leads to similar failure. In recent work, Sharma and Sharma (2021) found that the (in)action state and negative emotion can lead to procrastination, and an effortful selfregulated coping mechanism is needed to overcome the inner resistance.…”
Section: Emotional Reaction-handling Action Orientation and Wisdommentioning
confidence: 99%